The spread of invasive neophytes in the riparian vegetation of the Tichá Orlice - Hajzlerová, Lenka; Matějček, Tomáš (Journal for Geography, 2011)
This article summarises the observations and findings gained during the field survey of invasive neophytes in riparian vegetation of the river of Tichá Orlice in the Czech Republic. Seventeen taxa that could significantly load the riparian vegetation of the given area were chosen. A methodology of mapping and surveying which was designed by Matějček (2009) was applied. Using this methodology, neophytes were recorded in segments (500 m long parts of the river channel). The occurrence was expressed by the means of a logarithmic scale. Final data were evaluated with the aid of indexes for individual segments or groups of segments. As more parts of the river channel network of the Czech Republic have been mapped and surveyed this way, it is possible to compare the final data and results. In the riparian vegetation of the Tichá Orlice following plants were registered most frequently: Himalayan Balsam (Impatiens glandulifera), Small Balsam (Impatiens parviflora) and Reynoutria (Reynoutria sp. div.) The mapped part of the Tichá Orlice is, in comparison to other watercourses, belongs to the watercourses that are loaded with the invasive kinds of plants more than average.